Numerical Study of Acoustic-Electric Signal Conversion for GIS Discharge Detection and Structure Optimization for pMUT. (5th April 2023) - Si, Wen-Rong; Zhao, Ying-Ying; Hu, Zheng-Yong; Fu, Chen-Zhao; Wang, Bo; Yang, Jian
Abstract : With the development of microelectromechanical technology, the piezoelectric micromechanical ultrasonic transducer (pMUT) for ultrasonic detection of gas-insulated switchgear (GIS) breakdown discharge has become possible. In this article, the ultrasonic-solid-pMUT coupling simulation model was established to investigate the propagation process of ultrasonic waves in GIS enclosure and the conversion between ultrasonic and electric signals through pMUT. The output electric signals for the unsimplified top electrode and simplified top electrode model were compared, and the structure of receiving pMUT was optimized according to the main ultrasonic frequency range of GIS breakdown discharge and the key performance parameters of pMUT. First, it is found that the simulation results of the ultrasonic-solid-pMUT coupling model are reliable, and the frequency of the output electric signal of receiving pMUT is consistent with the input signal, while the amplitude of output signal attenuates greatly. Second, simplifying the top electrode of pMUT may lead to relatively large errors in simulation results. The output response of simplified pMUT is obviously weakened, and the inherent frequency is higher. Furthermore, it is noted that the pMUT inherent frequency ( f 0 ) is inversely proportional to the radius ( R ) of the piezoelectric layer and directly proportional to the substrate thickness ( d si ). When the coverage rate of the top electrode is between 30% and 80%, the pMUT effective electromechanical coupling coefficient (K e f f 2 ) is high and has a maximum value. Finally, it is indicated that the pMUT with the optimum structure is suitable for the detection of GIS breakdown discharge ultrasonic signals, and the K e f f 2 can be improved by 106.7%.